Changing Christian Paradigms and their Implications for Modern Thought - Knox, Crawford. (Numen Book Series, 1993)
Though the Bible and creeds have provided a compass for Christianity from earliest times, the frameworks of thought within which they have been understood have constantly changed, the contribution of Augustine to these changes being fundamental. This book traces, first, these changes chronologically and shows how they have led to the separation of religion and science, faith and reason, supernatural and natural, and so to current materialism: but also to radical alterations to our understanding of God and his relationship to the world. The second part shows in more detail how these changes have altered the significance of major features of Christian faith and led to serious incoherences. And the third part shows, not only how pre-Augustinian and Biblical understandings cohere closely with modern science, but that they have radical implications for our understanding of man, his place in nature and survival of death, for Jesus Christ and for the role of the Churches.